A quality improvement initiative to improve developmental screening in a high-risk follow-up clinic in western India - Kaur, Arshdeep; Sohane, Arpit; Chougula, Priyadarshini Virupaxi; Malshe, Nandini; Suryawanshi, Pradeep; Patnaik, Suprabha (Frontiers in Pediatrics, 2025)
IntroductionEarly childhood is a uniquely sensitive period for developing cognitive ability, language, social and motor development. Any disruption in the typical progression within these areas may result in developmental delays if not intervened timely, potentially causing various morbidities in a child and adversely affecting the quality of life for both the child and their family. Therefore, it is essential to conduct developmental screenings at regular recommended intervals.MethodsThis single-center quality improvement (QI) study was conducted in a tertiary care center with a level 3B neonatal intensive care unit, running a high-risk follow-up clinic. We aimed to improve the developmental screening in children (≤2 years) visiting the high-risk follow-up clinic, from the current 46.1% to ≥75% within three months. A quality improvement team conducted a root cause analysis for low screening rate, which led to the planning of several interventions. These included ensuring the consistent availability of Ages and Stages Questionnaire-3 (ASQ-3) screening forms in both regional and official languages, establishing a dedicated ASQ-3 counter, and conducting reinforcement and training sessions for interns and junior residents. Data was logged in the clinic record book and analyzed with statistical process control chart (P chart) and a run chart.ResultsThis QI project commenced in October 2023 and is still operational in a sustainable phase. During the study period, out of 1,368 eligible children, 1,259 (92%) underwent developmental screening using the ASQ-3 screening tool (process indicator). Developmental delay was detected in 196 children (15.5%), who were referred for early intervention (outcome indicator). Process was under statistical control, as evidenced by P charts.ConclusionThis QI project improved the clinic's ASQ-3 performance rate, thereby helping more children with developmental delay obtain early intervention.